2015
DOI: 10.1158/1535-7163.mct-14-0956
|View full text |Cite
|
Sign up to set email alerts
|

Effective Inhibition of Bone Morphogenetic Protein Function by Highly Specific Llama-Derived Antibodies

Abstract: Bone morphogenetic proteins (BMP) have important but distinct roles in tissue homeostasis and disease, including carcinogenesis and tumor progression. A large number of BMP inhibitors are available to study BMP function; however, as most of these antagonists are promiscuous, evaluating specific effects of individual BMPs is not feasible. Because the oncogenic role of the different BMPs varies for each neoplasm, highly selective BMP inhibitors are required. Here, we describe the generation of three types of lla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
3
15
0
1
Order By: Relevance
“…We recently generated 2 llama-derived BMP4-specific antibodies or VHHs, C4 and C8. 33 VHHs are single domain antibodies only composed by the variable domain of the heavy chain of a llama-derived antibody, which is around 15 kDa in size. Due to their unique structure and small size, VHHs can specifically bind with high affinity to their antigens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently generated 2 llama-derived BMP4-specific antibodies or VHHs, C4 and C8. 33 VHHs are single domain antibodies only composed by the variable domain of the heavy chain of a llama-derived antibody, which is around 15 kDa in size. Due to their unique structure and small size, VHHs can specifically bind with high affinity to their antigens.…”
Section: Resultsmentioning
confidence: 99%
“… 28 Surprisingly, the concentrations at which those antibodies were used in those and in other publications 29-31 ranged between 1-10 μg/ml, in contrast to the nanomolar range of which the VHH were shown to be biologically active. 33 To test whether these disparities are due to differences in experimental conditions or not, we compared the activity of C4C4 and C8C8 with current anti-BMP4 antibodies in the luciferase C2C12 system. These experiments confirmed that these antibodies are BMP4-specific, as only C8C8 inhibited BMP2-mediated signals ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calpe and colleagues (37) showed that neutralizing antibodies for BMP-4 increase the chemosensitivity of HT29 cells. Dorsomorphin was identified as a potent BMP inhibitor, and its analogue, DMH-1, Ã , P < 0.05; ÃÃ , P < 0.01; ÃÃÃ , P < 0.001, as determined by Student t test (A and C, bottom) or two-way ANOVA (C, top).…”
Section: Discussionmentioning
confidence: 99%
“…Для терапии онкологических процессов также были разработаны высокоселективные наноан-титела, связывающие и блокирующие активность костных морфогенетических белков разных ти-пов, которые участвуют как в физиологических, так и патологических процессах, в том числе кан-церогенезе и опухолевой прогрессии [19].…”
Section: наноантитела для терапии онкологических заболеванийunclassified